2002
DOI: 10.1177/156482650202300315
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status of Rural Women in Relation to their Participation in Mixed Farming in the Tafresh Area of Iran

Abstract: ISBN 0-8493-8736-1) 422 pages, hardcover. US$69.95/£46.99.Childhood obesity is increasing rapidly, not only in industrialized but also in developing countries in transition. It is cause for alarm that it commonly leads to adult obesity. Adult obesity is already endemic in most industrialized countries and is rapidly increasing in the more advanced developing countries as well. The result is an increase in morbidity and mortality from diabetes, hypertension, coronary heart disease, and other chronic diseases. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Total Sugar intakes: Some of the studies had estimated TS intakes at the national level for certain age groups (such as adults, children or adolescents), or for the entire population (i.e., per capita), while others had produced estimates pertinent to specific regions within countries [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. Table S3 presents data pertinent to TS intakes in countries of the region, whether these intakes were reported as g/day or % EI.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Total Sugar intakes: Some of the studies had estimated TS intakes at the national level for certain age groups (such as adults, children or adolescents), or for the entire population (i.e., per capita), while others had produced estimates pertinent to specific regions within countries [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. Table S3 presents data pertinent to TS intakes in countries of the region, whether these intakes were reported as g/day or % EI.…”
Section: Resultsmentioning
confidence: 99%
“…The study in Afghanistan reported a per capita estimate of 5% EI based on a 7-day food consumption recall [ 44 ], while the household budget survey conducted in Jordan reported an estimate of 11.8% EI [ 46 ] ( Figure 2 ). As for regional studies ( Figure 3 ), TS intake levels among adults were estimated at 13.5% EI and 14.7% EI in Palestine (West Bank) and Lebanon (Beirut) [ 55 , 61 ], respectively, and rural women in Iran (7.6%) [ 54 ], while being slightly higher among urban women in Egypt (16% EI) [ 53 ] ( Figure 3 ). Among the few countries that have evaluated TS intake among adolescents, Jordan (Amman) reported the highest levels (42–48% EI) [ 60 ], while Libya (Benghazi) reported the lowest (20.4% EI) [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the few studies that consider work intensity confirm its importance. For instance, Fami, Veerabhadraiah, and Nath (2002) and Higgins and Alderman (1997) show that women's energy balance is in deficit when they engage in intensive agricultural work.…”
Section: Implications For the Analysis Of Time Constraints And Time Pmentioning
confidence: 99%